Gastric Corpus Hypertrophy with a Bleeding Hyperplastic Polyp in a -naive Subject after Long-term Proton Pump Inhibitor Use - Jong Hyeon Jeong; Sun-Young Lee; Hye Seung Han (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2022)
A 22-year-old man presented with recurrent dizziness and melena. He had no remarkable medical history except for the reflux symptoms for which 18 months of proton pump inhibitor (PPI) intake was required. Gastroscopy revealed a 1-cm, blood-tinged polyp within the gastric rugae. A thickened gastric corpus was observed with a regular arrangement of collecting venules on its surface. Hyperplastic foveolar epithelium was observed in the biopsied specimens from the fundus and gastric rugae. The diagnosis after polypectomy was gastric hyperplastic polyp. Abdominal CT revealed hypertrophy only in the gastric corpus without antral involvement. Increased levels of serum pepsinogen I (>160 ng/mL), pepsinogen II (>50 ng/mL), chromogranin A (>1,800 ng/mL), and gastrin (534 pg/mL) were noted. Three months after PPI discontinuation, CT revealed improvement of the hypertrophic gastric corpus. Serum chromogranin A and gastrin levels decreased to 950.4 ng/mL and 517.0 pg/mL, respectively. Herein, we report a young, Helicobacter pylori-naive patient with prominent hyperplasia in the gastric corpus and a bleeding hyperplastic polyp after long-term PPI use.